SPIRITUAL AND MORAL EDUCATION OF TODAY'S YOUTH (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is about the spirituality of today's youth, their morals, education, the role of spirituality in the achievements and shortcomings of today's youth and the views of modern youth on society and its impact on the future.